CEO Horizon, Optimal Pay Duration, and the Escalation of Short‐Termism - MARINOVIC, IVAN; VARAS, FELIPE (Journal of Finance, 2019)
ABSTRACT This paper studies optimal contracts when managers manipulate their performance measure at the expense of firm value. Optimal contracts defer compensation. The manager's incentives vest over time at an increasing rate, and compensation becomes very sensitive to short‐term performance. This generates an endogenous horizon problem whereby managers intensify performance manipulation in their final years in office. Contracts are designed to encourage effort while minimizing the adverse effects of manipulation. We characterize the optimal mix of short‐ and long‐term compensation along the manager's tenure, the optimal vesting period of incentive pay, and the dynamics of short‐termism over the CEO's tenure.